2014
DOI: 10.1161/hypertensionaha.114.03782
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Characterization of the Underappreciated and Important Relationship Between Heart Rate Variability and Heart Rate

Abstract: Heart rate variability (beat-to-beat changes in the RR interval) has attracted considerable attention over the last 30+ years (PubMed currently lists >17,000 publications). Clinically, a decrease in heart rate variability is correlated to higher morbidity and mortality in diverse conditions, from heart disease to foetal distress. It is usually attributed to fluctuation in cardiac autonomic nerve activity. We calculated heart rate variability parameters from a variety of cardiac preparations (including humans, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
321
3
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 264 publications
(354 citation statements)
references
References 21 publications
18
321
3
12
Order By: Relevance
“…In contrast to these findings in premenopausal women, in postmenopausal women; 2) HF and LF remained suppressed below pre-exercise values at one hour post acute exercise; and 3) pre-treatment with chronic oral estrogen did not augment vagal modulation at rest, or enhance HRV recovery in the post-exercise period, suggesting delayed recovery of autonomic modulation. In view of recent concerns that these indices of HRV are simply a function of HR 25 , it is important to emphasize that these differences between premenopausal and postmenopausal women occurred despite identical heart rates after exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these findings in premenopausal women, in postmenopausal women; 2) HF and LF remained suppressed below pre-exercise values at one hour post acute exercise; and 3) pre-treatment with chronic oral estrogen did not augment vagal modulation at rest, or enhance HRV recovery in the post-exercise period, suggesting delayed recovery of autonomic modulation. In view of recent concerns that these indices of HRV are simply a function of HR 25 , it is important to emphasize that these differences between premenopausal and postmenopausal women occurred despite identical heart rates after exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Both systems, the constant hydrostatic pressure system and the constant flow system, do not normally permit the heart to generate pressure-volume work. 22 In both cases, this retrograde flow shuts the leaflets of the aortic valve so that the perfusion solution cannot enter the left ventricle. As mentioned above, most parts of the apparatus for Langendorff's heart perfusion are water-jacketed with warm circulating water to maintain the temperature of the perfusate and of the heart at constant temperature of 37°C.…”
Section: Setupmentioning
confidence: 99%
“…Various other electrodes which can be used include a suction, wick, and sewn-on contacts. 7,21,22 Cardiac contractile function and coronary flow are generally studied simultaneously. Any change in coronary flow also affects the contractility of the heart.…”
Section: 20mentioning
confidence: 99%
“…Furthermore, there are no details of how HRV was corrected for differences in HR; we assume they made a linear correction, which will be inadequate to correct for the nonlinear dependence of HRV on HR. 3 The importance of HR on observed changes in HRV can be estimated: Zaza et al 4 have independently shown that the natural log of standard deviation of normal-to-normal beats-log n (SDNN)-changes by 0.16 to 0.17 for every 10 beats per minute (bpm) change in HR; our own data yield a similar value. Figure 2) could be explained by a modest and plausible bradycardia (5.7 bpm decrease in the example given).…”
mentioning
confidence: 59%
“…2 It is established that time-and frequency-domain measures of HRV are nonlinearly dependent on HR, with low HRV being intrinsically linked to a higher HR, and vice versa. [3][4][5] We argue that HRV is a nonlinear surrogate of HR. Soares-Miranda et al recognized the dependence of HRV on HR, and stated that HR was evaluated as a "potential confounder or mediator" of HRV in a separate analysis by "adding a multiplicative interaction term and assessing the statistical significance of the Wald test".…”
mentioning
confidence: 97%